CARDIOMYOCYTE CELLULAR REGULATION ON EXERCISE - Vidiari, Indira (Sport and Fitness Journal; Vol 11 No 2 (2023): Volume 11, No.2, May 2023, 2023)
ABSTRACT   85% of deaths from cardiovascular disease are caused by CHD. More than 75% of deaths from cardiovascular disease occur in low- and middle-income countries. Myocardial injury caused by ischemia-reperfusion (IR) is a serious clinical problem. Reperfusion injury can cause damage or death to the myocardium and coronary vessel endothelium. Therefore it is necessary to develop a strategy in the field of cardiac regeneration, both for the prevention and curative of cardiovascular disease. Cellular reprogramming occurs in cardiomyocytes in response to physical exercise. Cardiomyocytes keep up with increased demand, reflecting that there is optimal energy potential and reserve capacity. It is often referred to as the ''athlete's heart''. Cardiac remodeling in response to chronic exercise to match the increased workload is by increasing heart size, in the absence of cardiomyocyte proliferation. This physiological growth is accompanied by an increase in energy production capacity, especially in mitochondria. Normal hypertrophic growth is characterized by normal contractile function at rest. This is in contrast to the pathological growth produced by prolonged hypertension or ischemic heart disease, in which contractile function and metabolic energy production are decreased. At the cellular and molecular level, it is clear that the activation of signaling pathways and the resulting transcriptional response different between physiological and pathological cardiac growth.